Prelacteal Feeding of Newborns in Postconflict Timor-Leste - Khanal, Vishnu; Lee, Andy; Nunes Brites da Cruz, J.; Karkee, R. (Lippincott Williams & Wilkins, 2014)
Objectives: The aim of the present study was to investigate the prevalence of prelacteal feeding and its associated factors in Timor-Leste using updated data from the national survey. Methods: Complex sample analysis was undertaken to account for the 2-stage cluster design of the Demographic and Health Survey 2009–2010. Backward stepwise logistic regression was conducted to ascertain factors associated with the prevalence of prelacteal feeding. Results: A total of 4821 mother–infant pairs were included in the analysis. The prevalence of prelacteal feeding was 12.3% (95% confidence interval [CI] 11.1–13.5). The most popular prelacteal food was plain water (50.7%), followed by glucose/sugar water (32.5%) and milk other than breast milk (22.7%). Older mothers (35–49 years), mothers with upper socioeconomic status, those who perceived their newborns as small size, and those residing in urban areas were approximately 1.5 times more likely to give prelacteal feeds, whereas women who followed religions other than Roman Catholic had twice the risk (adjusted odds ratio 1.98; 95% CI 1.16–3.41). Conclusions: Antenatal and postnatal counselling sessions that promote exclusive breast-feeding and discourage prelacteal feeding are needed that specifically target these vulnerable subgroups of Timorese mothers.